Penerapan Metode Pembelajaran Kooperatif Tipe Number Head Together (NHT) Pada Siswa Kelas XI IPS 2 SMA Negeri 2 Watampone Untuk Meningkatkan Hasil Belajar Bahasa Indonesia - jauhari jauhari (Universitas Negeri Makassar, 2019)
Abstract. The purpose of this study was to describe an increase in Indonesian language learning outcomes through cooperative learning method Number Head Together (NHT) in Class XI IPS 2 students at SMA 2 Watampone. This research approach, which is descriptive. The design or model of this research is Action Research. This research was carried out in Class XI IPS 2 of SMA Negeri 2 Watampone totaling 38 people. This research was conducted in the even semester 2016/2017. Data collection is done through observation, documentation, and test techniques. Data analysis techniques, namely quantitative descriptive analysis and qualitative descriptive analysis. The results showed that (1) the learning outcomes of students in the first cycle were categorized as medium with an average value of 64.15 and increased in the second cycle to be a high category with an average value of 77.89. Learning completeness in the first cycle was 44.73% and increased in the second cycle to 92.11%. Thus, the application of NHT cooperative learning can improve the learning outcomes of Indonesian students in Class XI IPS 2 at SMA 2 Watampone. (2) Cooperative learning NHT increases the student's effectiveness in learning. The indicator of improvement can be observed based on the learning outcomes of the first cycle and the second cycle which experience changes especially in changes in motivation, enthusiasm and values of students learning students understand the material.